2018
DOI: 10.1186/s13033-018-0186-2
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy: what do Nigerian adolescents know about depression?

Abstract: BackgroundDepression is a leading cause of disability and has been projected to become the 2nd most burdensome disease by the year 2020; depression has also been found to be the strongest single risk factor for attempted or completed suicides. Adolescent-onset mood disorders are frequently unrecognized or misdiagnosed and often go untreated. While there is a growing literature on the mental health literacy of adults, there has not been a parallel interest in the mental health literacy of young people in Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 26 publications
2
45
2
1
Order By: Relevance
“…This is consistent with findings from a similar study carried out among teachers in India (Mendonsa & Shihabuddeen, ). This also shows that teachers surveyed did not differ significantly from the general Nigerian populace including students in terms of poor knowledge of depression (Adeosun Ibukun, ; Aluh, Anyachebelu, Anosike, & Anizoba, ; Andrew, Igboanusi, Joshua, & Yakubu, ; Dogra et al, ). Corresponding with a study by Rothì, Leavey, and Best (), there was no association between experience and ability to correctly identify depression.…”
Section: Discussionmentioning
confidence: 75%
“…This is consistent with findings from a similar study carried out among teachers in India (Mendonsa & Shihabuddeen, ). This also shows that teachers surveyed did not differ significantly from the general Nigerian populace including students in terms of poor knowledge of depression (Adeosun Ibukun, ; Aluh, Anyachebelu, Anosike, & Anizoba, ; Andrew, Igboanusi, Joshua, & Yakubu, ; Dogra et al, ). Corresponding with a study by Rothì, Leavey, and Best (), there was no association between experience and ability to correctly identify depression.…”
Section: Discussionmentioning
confidence: 75%
“…Many published studies have found that alexithymia has an adverse effect on adolescents' mental health [35,36]. At the same time, low levels of health literacy also increase adolescents' risk of physical and psychical problems [37][38][39]. It may be that adolescents with low levels of health literacy are not recognizing signs of negative emotion and cannot seek timely mental health services, resulting in deterioration of mental health, in line with Beck's cognitive theory, which indicates that an individual's negative automatic thoughts may affect emotional, physical, and motivational symptoms of depression [40].…”
Section: Discussionmentioning
confidence: 99%
“…The situation is more severe in Africa, as proved by a study among Nigerian students where very few students (1.5%) considered seeking help from a professional (e.g. psychiatrist or psychologist) as a recommended course of action for depression [37]. These students most commonly preferred friends and families as sources of help [37].…”
Section: Introductionmentioning
confidence: 99%
“…psychiatrist or psychologist) as a recommended course of action for depression [37]. These students most commonly preferred friends and families as sources of help [37]. Despite the adverse consequences of CMDs, most students do not seek help or prefer informal sources of help than formal sources [3841].…”
Section: Introductionmentioning
confidence: 99%